2021
DOI: 10.1002/fsn3.2415
|View full text |Cite
|
Sign up to set email alerts
|

Study on starch content detection and visualization of potato based on hyperspectral imaging

Abstract: Potatoes contain nutrients such as vitamin C, vitamin B6, folic acid, potassium, iron, and magnesium (Ji et al., 2019). With an annual global output of approximately 400 million metric tons, potatoes have become one of the four major global food crops, according to the United Nations Food and Agriculture Organization. They are mainly processed into various products, including frozen or dehydrated potatoes, potato chips, and potato starch (Rady et al., 2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…Meanwhile, in this study, the significant differences in the prediction results of different screening methods were found, and especially showed the suitability of IVSO and MASS methods and inefficiency of SPA selection for effective wavelengths in prediction of three chemical indexes of HJ samples. Interestingly, the former reports also showed that starch content in potato was well predicted based on effective wavelengths selected via IVSO method, with R 2 values > 0.88 in both calibration and prediction sets, and RPD values > 2.0 in almost all groups when combined with regression models (Wang et al, 2021a). Similar to our results, total phenolics, flavonoids, and anthocyanins contents in dry black goji berries (Lycium ruthenicum Murr.)…”
Section: Comparison and Analysis Of Three Methods On Selection E Ecti...supporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, in this study, the significant differences in the prediction results of different screening methods were found, and especially showed the suitability of IVSO and MASS methods and inefficiency of SPA selection for effective wavelengths in prediction of three chemical indexes of HJ samples. Interestingly, the former reports also showed that starch content in potato was well predicted based on effective wavelengths selected via IVSO method, with R 2 values > 0.88 in both calibration and prediction sets, and RPD values > 2.0 in almost all groups when combined with regression models (Wang et al, 2021a). Similar to our results, total phenolics, flavonoids, and anthocyanins contents in dry black goji berries (Lycium ruthenicum Murr.)…”
Section: Comparison and Analysis Of Three Methods On Selection E Ecti...supporting
confidence: 91%
“…Many previous similar reports have shown that effective HSI wavelengths often have the same or better prediction results for chemical indexes compared with those from the full wavelength group. The examples can be studies on starch and water contents prediction in potato (Xiao et al, 2020;Wang et al, 2021a), total caffeine and theanine contents prediction from tea (Wang et al, 2020(Wang et al, , 2021c, amylose and amylopectin contents prediction in sorghum (Huang et al, 2021b), and total anthocyanin content and antioxidant activity prediction in mulberry fruit (Huang et al, 2017). The results of this research showed that the prediction effect of selection wavelengths groups was the same as or even better than that from the full wavelengths groups.…”
Section: Comparison and Analysis Of Three Methods On Selection E Ecti...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of Mendez et al (2019) and Hershberger et al (2022). They reported a marginal improvement in predictive ability for SVM over PLS, contradicting Ludwig et al (2019) and Wang et al (2021) who found SVM superior to PLSR. The observed variation in algorithm performance between studies could be attributed to differences in the trait investigated, data distribution, and sample variability (Frizzarin et al, 2021).…”
Section: Assessment Of Model Predictionsupporting
confidence: 89%
“…Then, the starch content (SC) of different potato varieties was determined based on linear PLSR and nonlinear support vector regression (SVR) models. Based on selected feature wavelengths, the CARS-SVR model achieved the highest accuracy with the R P of 0.93 [ 74 ]. Besides the whole potato, the SC of fresh-cut potato slices was also measured.…”
Section: Applications For Tuber Quality Assessmentmentioning
confidence: 99%